(untitled) (Dissertare, 2021)
Historically, people have been forced through 28 stock market crashes and more than 14 global recessions, the largest of which was caused by greed, irresponsibility, and unethical behavior by economic and political decision makers (Dell’Ariccia , Igan and Laeven, 2008; López Fdez de Lascoiti, 2009; Pérez, 2011). Faced with these situations, the first objective of this article is to analyze the importance of strengthening the ethical behavior of leaders in organizations. On the other hand, as a second major objective, there is a need to develop an adequate training and educational process that guides and affirms the personal values of people and, in particular, of leaders in the organizational context. The methodological approach adopted is qualitative, with a documentary design supported by bibliographic review and critical analysis. The conclusions highlight the need to strengthen the responsible behavior of leaders through comprehensive training processes that emphasize ethical aspects of behavior, which requires the contribution of formal education - school and university - in conjunction with the training provided by the organizations, through the formation of a long-term strategic alliance, which can offer as a final result, the development of people who act in accordance with the exercise of ethical leadership.